Protective effects of recombinant Brucella abortus Omp28 against infection with a virulent strain of Brucella abortus 544 in mice - Lim, Jeong Ju (The Korean Society of Veterinary Science, 2012)
The outer membrane proteins (OMPs) of Brucella (B.) abortus have been extensively studied, but their immunogenicity and protective ability against B. abortus infection are still unclear. In the present study, B. abortus Omp28, a group 3 antigen, was amplified by PCR and cloned into a maltose fusion protein expression system. Recombinant Omp28 (rOmp28) was expressed in Escherichia coli and was then purified. Immunogenicity of rOmp28 was confirmed by Western blot analysis with Brucella-positive mouse serum. Furthermore, humoral- or cell-mediated immune responses measured by the production of IgG1 or IgG2a in rOmp28-immunized mice and the ability of rOmp28 immunization to protect against B. abortus infection were evaluated in a mouse model. In the immunogenicity analysis, the mean titers of IgG1 and IgG2a produced by rOmp28-immunized mice were 20-fold higher than those of PBS-treated mice throughout the entire experimental period. Furthermore, spleen proliferation and bacterial burden in the spleen of rOmp28-immunized mice were approximately 1.5-fold lower than those of PBS-treated mice when challenged with virulent B. abortus. These findings suggest that rOmp28 from B. abortus is a good candidate for manufacturing an effective subunit vaccine against B. abortus infection in animals.